How to care for a human girl : a novel - Wurzbacher, Ashley, 1985- (Atria Books, 2023)
"From "a writer at the top of her game" (The New York Times) comes a bighearted and sharply funny debut novel about two estranged sisters and the crossroads they face after becoming unexpectedly pregnant at the same time. Two years after the death of their mother, Jada and Maddy Battle both navigate unplanned pregnancies. Jada, a thirty-one-year-old psychology PhD student living in Pittsburgh, quietly obtains an abortion without telling her husband, but the secret causes turmoil in her already shaky marriage. Back home in rural Pennsylvania, nineteen-year-old Maddy, who spends her time caring for birds at a wildlife rehabilitation center, is paid off by the man who got her pregnant to get an abortion. But an unsettling visit to a crisis pregnancy center adds to her doubts about whether to go through with it. Although Maddy still hasn't forgiven Jada for a terrible betrayal, she goes to her for support, only to discover the cracks in the façade of her sister's seemingly perfect life. As their past resentments boil over, the sisters must navigate the consequences of their choices and determine how best to care for themselves and each other. With luminous prose and laser-sharp psychological insight, How to Care for a Human Girl is a compassionate and unforgettable examination of the complexities of choice, the special intimacy of sisterhood, and the bizarre ways our heated political moment manifests in daily life"--